(untitled) (ELang | An English Language Education Journal, 2022)
This research paper is entitled “The Effectiveness of Know, Wnat, Learned (KWL) strategy to improve reading ability in descriptive text (A Pre-Experimental study done in the Second grade student of junior high school)”. The aim of the reseach is to know whether or not there is significant difference in the students’ score before and after the treatment by using KWL strategy to imfrove their reding ability in descriptive text and to find out the students’ responses through the use of KWL strategy to imfrove their reding ability in descriptive text. The population of this research is the second grade of junior SMPN 2 Banjaran, which consists of 11 class from class A to class K. The writer take 38 students’ as the sample of study. The sample of this reaseach is class B. In this study there is one group, the pre-experiment based on one group pre-test – post-test design was used in this research. The results of the pre-test and post-test were there was difference score after being taught by KWL strategy and significant improvement of the students’ reading ability. The aspect which was influenced the most was identifying main idea. From the computation of pre-test and post-test score the result shows that white the degree of freedom (df)= N ? 1 = 38 ?1 = 37, at p = .05 of two tailed, the value of t-table = 2.042. As the derived t is bigger than that of the t-table (3.971 > 2.021), This means that teaching reading descriptive text using KWL strategy in the second grade of SMPN 2 Banjaran is effective and the students also like being taught with KWL strategy in learning reading descriptive text. It is also supported by the students’ response in questionnaires. The result showed 38 students agree that KWL strategy helped them in understanding the material that was given by teacher, and helped them to understand and found the main ideas from a descriptive text by using KWL strategy. It means the students response is positive about KWL strategy. Key word : KWL strategy, Reading, descriptive text.